STRENGTHENING FINANCIAL STABILITY IN THE MANAGEMENT OF THE ECONOMIC POTENTIAL OF THE ENTERPRISE - GONCHAR, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Features of the formation of financial stability of industrial enterprises in the conditions of war and global modern challenges of the market are summarized. The key problems faced by enterprises in war conditions and the factors that shape their financial stability are identified and grouped. It is summarized that in the conditions of military operations on the territory of the country, for many economic enterprises, slightly reduced indicators of financial stability are accepted within the permissible limits, provided that business security is ensured. It was concluded that the strengthening of financial stability and regulation of liquidity in modern conditions are primarily focused on the payment of wages, with the calculation of labor resources that ensure the production of products, the stability of the enterprise's resources, the effective use of potential, ensuring the solvency and liquidation of the enterprise.A conclusion was made about the influence of effective financial management on the level of financial stability. In the conditions of limited involvement of financing sources, the financial stability and liquidity of the enterprise increases significantly. Requirements for the solvency of enterprises are increasing. Businesses that do not have their own resources should not function. Financial stability is the main condition for life activity and the realization of the economic potential of industrial enterprises and a certain characteristic of the effectiveness of activities in war conditions.
Keywords: enterprise; evaluation; financial security; financial stability; management